Duolingo and Learner Autonomy: Investigating The Role of Personalization and Gamification in Promoting Self-directed Language Learning - Sari Mahibatus Saniyah (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
The purpose of this research is to investigate and seeks to explore how these features promote learner autonomy, and how these features can be optimized to enhance the effectiveness of language learning platforms. The kind of the research is mix-methods and the type is using explanatory sequential design. The data quantitative is taken first after that data qualitative. How to collect data through 2 types : (1) questionnaire about the participants' use of personalization and gamification features in Duolingo, autonomy, and language learning outcomes (2) interview about the participants' perceptions of how personalization and gamification features have affected their autonomy and learning outcomes. The research subjects consisted of 32 respondents from grade 7 students at SMPN 2 Sukowono while for interviews, 3 students were selected to be interviewed based on the score of the questionnaire that received the highest score. Based on the results of the questionnaire, shows that students are at mediate level. So the impact of personalization in self-directed language learning namely the students agree that in the heart feature where if the user makes a mistake their life will run out to play Duolingo again so the user will rest and review the previous lesson before continuing to get another heart. Another impact of personalization was today's review feature on Duolingo. The students agreed that the feature was easier to find out mistakes and correct wrong answers when working on practice questions. Then the impact of gamification in self-directed language learning namely the students strongly agree that the leaderboard feature made them target score and ranking on Duolingo. The second impact was the students agree that were sure to do exercises in Duolingo without a dictionary and translation feature on Duolingo. Next, the students agreed that after using Duolingo, they can know the correct grammar as well. And the last impact was the students agree that they have difficulty in several levels of Duolingo.Students’ perceptions of the use of personalization and gamification on Duolingo in self-directed language learning some of the features that helped them while using Duolingo, such as the translation feature, included the use of gamification in self-directed language learning. They found the translation function helpful in helping them learn new vocabulary. Along with the translation feature, Duolingo players can also develop their speaking and listening skills. They can pronounce the appropriate words and understand what the narrator was saying throughout the talk. Users can view their ranking on the leaderboard within Duolingo. Further, users can set a daily score value. Several of the students in this interview had set goals for their Duolingo grades, while one had not.